Pengaruh Pemberian Ransum Pelet Berbasis Limbah Sawit terhadap Konsumsi, Kecernaan Serat Kasar dan Lemak Kasar Pada Kambing Kacang: The Effect of Feeding Palm Waste-Based Pelleted Rations on Consumption, Digestibility of Crude Fiber and Crude Fat in Lokal Katjang Goats - Luber, Yusuf Amirullah; Afdal, M; Adriani, Adriani; Saad, Wan Zuhainis; Wibowo, Sarwo Edy; Darlis, Darlis (Fakultas Peternakan Universitas Jambi, 2025)
Background: Katjang goats are an indigenous Indonesian breed with promising potential for development; however, their growth is highly influenced by feed quality. Palm oil waste is now being utilized as an alternative feed source due to its abundance and nutritional value. Processing it into pellets aims to enhance palatability, distribution, and nutrient stability. Further research is needed to evaluate the effects of palm oil waste pellets on consumption, Crude Fiber (CF) and Ether Extract (EE) digestibility in Katjang goats, in order to support the optimization of local feed resources. Purpose: This study aims to analyze the effects of oil palm waste-based pellet feed on feed intake, CF and EE digestibility in Kacang goats. Methods: This study employed a Randomized Block Design (RBD) with four treatments: P0 (90% kumpai grass + 10% rice bran), P1 (60% kumpai grass + 30% oil palm waste + 10% rice bran), P2 (30% kumpai grass + 60% oil palm waste + 10% rice bran), and P3 (90% oil palm waste + 10% rice bran). The observed variables included feed intake, CF, and EE digestibility (digestibility analysis followed the AOAC 2005 method). The collected data were analyzed using analysis of variance (ANOVA). Results: The results of the analysis of variance showed that the administration of palm oil waste pellets had a significant effect (P<0.05) on consumption, Crude Fiber (CF) and Ether Extract (EE) digestibility. The results indicated that the P2 treatment yielded the highest feed intake (474.60 g/head/day). However, CF and EE digestibility tended to decrease with increasing proportions of oil palm waste, especially in P3. Conclusion: The inclusion of 60% oil palm waste in pelletized feed can enhance all feed intake and the digestibility of crude fiber and crude fat.